2021
DOI: 10.1039/d1sm00592h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mobility and crystallization of renewable poly(ethylene furanoate) in situ filled with carbon nanotubes and graphene nanoparticles

Abstract: We investigate the thermal transitions and molecular mobility in new nanocomposites of biobased poly(ethylene furanoate) (PEF), by calorimetry and dielectric spectroscopy, supplemented by X-ray diffraction, Fourier transform infra-red spectroscopy and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 90 publications
2
24
0
Order By: Relevance
“…Specifically, it only displayed a small melt crystallization peak at a cooling rate of 5 °C/min and the amorphous samples could easily be obtained through a melt-quenching process. , As for PPF, Zhou et al did not even detect its melting point due to the slow crystallization rate . Incorporating the nanofillers into polyester matrices has been proven to be an effective way to increase the crystallization rate of furan-based polyesters. Papageorgiou et al reported the preparation of PEF-based composites through an in situ polycondensation method with multiwalled carbon nanotubes (MWCNTs). For the sake of comparison, functionalized MWCNTs and graphene oxide were also used to prepare the nanocomposites, while Wu et al used montmorillonite (MMT) as the nucleation agent. , All nanofillers accelerated the crystallization rate of PEF.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it only displayed a small melt crystallization peak at a cooling rate of 5 °C/min and the amorphous samples could easily be obtained through a melt-quenching process. , As for PPF, Zhou et al did not even detect its melting point due to the slow crystallization rate . Incorporating the nanofillers into polyester matrices has been proven to be an effective way to increase the crystallization rate of furan-based polyesters. Papageorgiou et al reported the preparation of PEF-based composites through an in situ polycondensation method with multiwalled carbon nanotubes (MWCNTs). For the sake of comparison, functionalized MWCNTs and graphene oxide were also used to prepare the nanocomposites, while Wu et al used montmorillonite (MMT) as the nucleation agent. , All nanofillers accelerated the crystallization rate of PEF.…”
Section: Introductionmentioning
confidence: 99%
“…Double melting peaks have been attributed to the melting recrystallization and remelting of the polymer chains, the presence of crystal modifications, such as two different crystal phases, the different lamellar thickness or crystal imperfections of the formed crystals, and species with different molecular weights. Considering that the XRD patterns of the semicrystalline prepared materials presented in our previous work [ 24 ] do not imply the presence of two different crystal phases, and the fact that the PEF/GNPs do not present with a cold crystallization peak, the double melting behavior is most probably connected to the formation of imperfect crystals with different lamellar thicknesses. These crystals have less thermal stability and melt at lower temperatures, inducing the earlier secondary melting peak [ 11 , 30 ].…”
Section: Resultsmentioning
confidence: 84%
“…Prior to the study of the crystallization of all the prepared materials, their molecular weights were calculated through intrinsic viscosity measurements and published in our previous work [ 24 ]. The reported M n (g/mol) for the neat PEF, PEF/0.5 GNPs, PEF/1 GNPs, and PEF/2.5 GNPs are 12 × 10 3 , 7 × 10 3 , 11 × 10 3 , and 7 × 10 3 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Kourtidou et al introduced carbon nanotubes and graphene nanoplatelets into PEF, resulting in promoted crystallization by enhancing nucleation and altering the free volume of the polymer, which is important for optimizing the mechanical performance and regulating the permeation of gas molecules. 22 Unfortunately, there are few reports about the regulation of the PEF gas barrier properties.…”
Section: Introductionmentioning
confidence: 99%